(untitled) (The Research of Medical Science Review, 2025)
In low-income countries, it is a well-accepted fact that iron deficiency anemia (IDA) during pregnancy adds to the risk of adverse maternal and fetal outcomes such as low birth weight and small for gestational age (SGA) outcomes. There is limited evidence on the period when anemia, especially early T3 IDA, and its singular association with fetal growth become pertinent. To evaluate the effect of early third-trimester IDA on birth weight and SGA birth, this retrospective cohort study, performed at [Institution Name], included a group of pregnant women. It was observed that early third-trimester IDA had a major effect on the incidence of LBW and SGA, emphasising the necessity of early screening and management. Pregnant women's iron supplementation should be more focused to enhance maternal and fetal health.